2019
DOI: 10.3390/brainsci9110303
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of C6 Glia-Precursor Cells In Vitro Differentially Modulates Gene Expression Related to Chronic Pain Pathways

Abstract: Glial cells comprise the majority of cells in the central nervous system and exhibit diverse functions including the development of persistent neuropathic pain. While earlier theories have proposed that the applied electric field specifically affects neurons, it has been demonstrated that electrical stimulation (ES) of neural tissue modulates gene expression of the glial cells. This study examines the effect of ES on the expression of eight genes related to oxidative stress and neuroprotection in cultured rode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…14,15 It is known that spinal cord stimulation (SCS) can modulate transcriptomic expression of neural cells in animal models. 8,9,12,13,[32][33][34][35][36] More specifically, our work demonstrated that changes in SCS stimulation parameters could differentially modulate gene expression of neurons and glial cells by using an approach with multiplexed electrical signals (called differential target multiplexed programming, DTMP). DTMP can modulate biological processes associated with neuron-glial interactions more effectively than other standard SCS approaches using high rate or low rate programs (HRP or LRP), while providing significant relief from thermal and mechanical hypersensitivity, which was also significantly improved relative to these standard SCS treatments.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…14,15 It is known that spinal cord stimulation (SCS) can modulate transcriptomic expression of neural cells in animal models. 8,9,12,13,[32][33][34][35][36] More specifically, our work demonstrated that changes in SCS stimulation parameters could differentially modulate gene expression of neurons and glial cells by using an approach with multiplexed electrical signals (called differential target multiplexed programming, DTMP). DTMP can modulate biological processes associated with neuron-glial interactions more effectively than other standard SCS approaches using high rate or low rate programs (HRP or LRP), while providing significant relief from thermal and mechanical hypersensitivity, which was also significantly improved relative to these standard SCS treatments.…”
Section: Introductionmentioning
confidence: 88%
“… 10 , 11 Recently, our lab and others have shown, using transcriptomics and proteomics in animal models, that neuropathic pain induces a complex response composed of metabolic, inflammatory, and immune biological processes involved in neuron-glial interactions that SCS can modulate. 8 , 9 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…Activation of neurogenic regulation of cardiac function [109][110][111] or brain clearance [112] including electrical stimulation of perivascular innervation [113] is distinct from the direct BBB polarization of Principle 2. Electrical stimulation of glia [114][115][116] and subsequent astrocyte regulation of the BBB [117] are also parallel but distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Brain heart infusion media (BHI) supplemented with penicillin, streptomycin, and hemin was used for L. tarentolae culturing following the method of Morgenthaler et al [ 97 ]. Axenic Rattus norvegicus C6 glioma cells (ATCC CCL-107) were cultured in FALCON 6-well culture plates using high glucose Dulbecco’s Modified Eagles Medium (incomplete DMEM; Sigma Life Sciences D6429; St. Louis, MO, USA) supplemented with 15% ( v / v ) horse serum (ATCC; Manassas, VA, USA) and 5% ( v / v ) heat-treated fetal bovine serum (GIBCO; Waltham, MA, USA) (now designated as complete DMEM) at 37 °C and maintained under a 5% CO 2 atmosphere following the method of Vallejo et al [ 98 ]. For experimentation, cells were harvested by trypsinization, following the manufacturer’s recommendations (Sigma Aldrich), and resuspended in complete DMEM.…”
Section: Methodsmentioning
confidence: 99%